A Comparative Study of Radiofrequencies Field Levels of Some Base Stations in Makurdi and its Environs in Benue State, North Central Nigeria - Iortile, J.T; Alumuku, L (International Journal of Natural Sciences Research, 2014)
A comparative study of radiofrequencies field levels of some base stations in Makurdi and its environs was carried out in Makurdi, Benue State, North central Nigeria. Electromagnetic field tester (EMF 827 Lutron) was used for measurement at distances ranging from 5.00, 10.00, 15.00 and 20.00 meters away from the base stations at the North, South, West and East directions. Electric field intensity and specific absorption rate (SAR) were calculated with reference to the human tissues. The result indicates that the average magnetic field levels of GLO and ZAIN base stations ranged between 0.10µT to 0.16µT. The mean electric field values for eye, brain and muscles ranged between 20.90〖vm〗^(-1) to 35.20〖vm〗^(-1). The specific absorption rate (SAR) ranged between 0.22〖Wkg〗^(-1) to 1.17〖Wkg〗^(-1). The GSM base stations under study conform to the standards set by regulatory agencies which pose no threat to residents located within the base station areas.